Chantal Akerman y el espíritu de los setenta - Janet Bergstrom (Universitat de Barcelona, 2001)
This article studies the cinematographic career of Chantal Akerman by placing it within the feminist context of the seventies. In fact,Jeanne Dielman, for instance, was described by Le Monde (January 1976) as “the first masterpiece in the feminine in the history of the representational status of a woman –her desire, her self-image, the image that others create of and for her. Her films have provided different answers to the question “who speaks?”, when the female voice/image is analysed. It is precisely as a question that this feminist film theory, as any definitive answer will always be simplistic. Akerman has shown, in a nondidactic manner, the fragile representational status of “woman” (daughter, mother, etc.) once it is removed from conventional cinematographic usage. Were these questions, so urgently posed during the seventies in women’s films and feminist theory, ever answered? Probably not, despite different attempts to remove “woman’s discourse” or “woman’s voice” from the discussion field, as these questions seem to be posed again by a new generation.